Women's career strategy choices and fertility in different welfare regime contexts - Schleutker, Elina (2012)
The comprehensive aim of this study is to increase the understanding of the cross-country differences in low fertility. In particular, the study discusses the interaction between women´s preferences, family policy, female labor force participation and fertility. The central argument of the thesis is that women, driven by their preferences but constrained by family policies and household’s resources, choose between three different types of strategies concerning work and family. In the empirical part of the thesis longitudinal data is employed to study women´s career strategy choices in Germany, the UK, and Finland. In all three countries a substantially large share of the women has remained outside the labor market for longer periods and has high average fertility (“homemaking career”). The largest share of the women have combined work and children with shorter absences from the labor market (“combination strategy”). Finally, a considerable share of the women have been working/studying continuously and have low fertility (“career strategy”). All in all, the study adds to the literature on women´s heterogeneous work-family decisions and suggests that future research on fertility should concentrate more on the heterogeneity in women´s preferences and choices.